2012
DOI: 10.1101/gr.134841.111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ADARs on small RNA processing pathways in C. elegans

Abstract: Adenosine deaminases that act on RNA (ADARs) are RNA editing enzymes that convert adenosine to inosine in doublestranded RNA (dsRNA). To evaluate effects of ADARs on small RNAs that derive from dsRNA precursors, we performed deep-sequencing, comparing small RNAs from wild-type and ADAR mutant Caenorhabditis elegans. While editing in small RNAs was rare, at least 40% of microRNAs had altered levels in at least one ADAR mutant strain, and miRNAs with significantly altered levels had mRNA targets with correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 49 publications
5
62
2
Order By: Relevance
“…Our data revealed that RNA editing has little correlation with mRNA expression changes in ADAR1 KD H9 cells (Supplementary information, Figure S4 and data not shown), which is in consistency with recent reports in other organisms [18][19][20]. We hypothesized that ADAR1 deficiency may lead to an altered miRNA repertoire, which in turn regulates mRNA expression in H9 cells and during differentiation.…”
Section: Adar1 Knockdown Dramatically Alters Mirna Repertoiressupporting
confidence: 78%
See 3 more Smart Citations
“…Our data revealed that RNA editing has little correlation with mRNA expression changes in ADAR1 KD H9 cells (Supplementary information, Figure S4 and data not shown), which is in consistency with recent reports in other organisms [18][19][20]. We hypothesized that ADAR1 deficiency may lead to an altered miRNA repertoire, which in turn regulates mRNA expression in H9 cells and during differentiation.…”
Section: Adar1 Knockdown Dramatically Alters Mirna Repertoiressupporting
confidence: 78%
“…It has been shown that at least 40% of miRNAs have altered levels in ADAR mutant C. elegans strains, although editing in small RNAs is rare [20]. Interestingly, a recent report found that despite the presence of a few sites in which editing is clearly beneficial, human RNA editing sites in coding regions are generally nonadaptive and evolutionarily poorly conserved, arguing against the physiological significance of these editing events in human [56].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…One potential clue is the recent observation that a specific subset of 26G siRNA maps to both introns and exons of its target transcripts, suggesting that siRNA of this class can be triggered by incompletely spliced mRNA precursors. 49 A further motivation is the recent finding that nematode spliceosome components are enriched among proteins whose phylogenetic conservation correlates with that of RNA silencing factors. 48 Since proteins with similar conservation tend to act in the same pathways, 50 this finding suggests a conserved connection between splicing and small RNA function.…”
Section: Splicing Factors Are Required For Sirna Production In C Elementioning
confidence: 99%